Answers

2014-03-05T18:18:01+05:30
1. (a+b)2 = a2 + 2ab+b2; a2 +b2 = (a+b)2 −2ab2. (a−b)2 = a2 −2ab+b2; a2 +b2 = (a−b)2 + 2ab3. (a+b+c)2 = a2 +b2 +c2 + 2(ab+bc+ca)4. (a+b)3 = a3 +b3 + 3ab(a+b); a3 +b3 = (a+b)3 −3ab(a+b)5. (a−b)3 = a3 −b3 −3ab(a−b); a3 −b3 = (a−b)3 + 3ab(a−b)6. a2 −b2 = (a+b)(a−b)7. a3 −b3 = (a−b)(a2 +ab+b2)8. a3 +b3 = (a+b)(a2 −ab+b2)
2 5 2
2014-03-05T18:27:45+05:30
(a+b)2 = a2 + 2ab+b2;
 a2 +b2 = (a+b)2 −2ab2.
 (a−b)2 = a2 −2ab+b2;
 a2 +b2 = (a−b)2 + 2ab3.
 (a+b+c)2 = a2 +b2 +c2 + 2(ab+bc+ca)
. (a+b)3 = a3 +b3 + 3ab(a+b)
 a3 +b3 = (a+b)3 −3ab(a+b)
. (a−b)3 = a3 −b3 −3ab(a−b)
 a3 −b3 = (a−b)3 + 3ab(a−b)
. a2 −b2 = (a+b)(a−b)
. a3 −b3 = (a−b)(a2 +ab+b2)
. a3 +b3 = (a+b)(a2 −ab+b2)
1 5 1